Active control of Alfvén eigenmodes in magnetically confined toroidal plasmas. (29th March 2019) - Garcia-Munoz, M; Sharapov, S E; Van Zeeland, M A; Ascasibar, E; Cappa, A; Chen, L; Ferreira, J; Galdon-Quiroga, J; Geiger, B; Gonzalez-Martin, J; Heidbrink, W W; Johnson, T; et al.
Abstract: Alfvén waves are electromagnetic perturbations inherent to magnetized plasmas that can be driven unstable by a free energy associated with gradients in the energetic particles' distribution function. The energetic particles with velocities comparable to the Alfvén velocity may excite Alfvén instabilities via resonant wave–particle energy and momentum exchange. Burning plasmas with large population of fusion born super-Alfvénic alpha particles in magnetically confined fusion devices are prone to excite weakly-damped Alfvén eigenmodes (AEs) that, if allowed to grow unabated, can cause a degradation of fusion performance and loss of energetic ions through a secular radial transport. In order to control the fast-ion distribution and associated Alfvénic activity, the fusion community is currently searching for external actuators that can control AEs and energetic ions in the harsh environment of a fusion reactor. Most promising control techniques are based on (i) variable fast-ion sources to modify gradients in the energetic particles' distribution, (ii) localized electron cyclotron resonance heating to affect the fast-ion slowing-down distribution, (iii) localized electron cyclotron current drive to modify the equilibrium magnetic helicity and thus the AE existence criteria and damping mechanisms, and (iv) externally applied 3D perturbative fields to manipulate the fast-ion distribution and thus the wave drive. Advanced simulations help to identify the key physics mechanisms underlying the observed AE mitigation and suppression and thus to develop robust control techniques towards future burning plasmas.